Opposing Functions of Heparanase-1 and Heparanase-2 in Cancer Progression. Issue 1 (January 2018) - Vlodavsky, Israel; Gross-Cohen, Miriam; Weissmann, Marina; Ilan, Neta; Sanderson, Ralph D.
Abstract : Heparanase, the sole heparan sulfate (HS)-degrading endoglycosidase, regulates multiple biological activities that enhance tumor growth, metastasis, angiogenesis, and inflammation. Heparanase accomplishes this by degrading HS and thereby regulating the bioavailability of heparin-binding proteins; priming the tumor microenvironment; mediating tumor–host crosstalk; and inducing gene transcription, signaling pathways, exosome formation, and autophagy that together promote tumor cell performance and chemoresistance. By contrast, heparanase-2, a close homolog of heparanase, lacks enzymatic activity, inhibits heparanase activity, and regulates selected genes that promote normal differentiation, endoplasmic reticulum stress, tumor fibrosis, and apoptosis, together resulting in tumor suppression. The emerging premise is that heparanase is a master regulator of the aggressive phenotype of cancer, while heparanase-2 functions as a tumor suppressor. Trends: Compelling evidence ties heparanase enzymatic and non-enzymatic activities with tumor initiation, growth, metastasis, and chemoresistance. Studies emphasize the impact of host heparanase on tumor progression, supporting the clinical use of antiheparanase therapy in combination with conventional anticancer drugs. The heparanase–syndecan–syntenin axis regulates exosome formation and hence provides a mechanism for the crosstalk between tumor cells, the host, and the tumor microenvironment. Heparanase-inhibiting compounds are being examined in cancer patients. Hpa2 inhibits heparanase activity and regulates the expression of selected genes that affect tumor angiogenesis, tumor fibrosis, cell differentiation, ER stress, and apoptosis of cancer cells, together resulting in tumor suppression. Heparanase-1 and -2 have multiple functions in health and disease in a context-dependent manner. The crystal structure of heparanase has been solved, paving the way for rational design of heparanase-inhibiting small molecules and monoclonal antibodies.